English Vocabulary in Use : Uper - intermediate - McCarthy, Michael (Đà Nẵng, 2002)
This book was written to help you to improve your English vocabulary. It will help you to learn not only the meaning of words but also how they are used. You can use this book either with a teacher or for self-study. In most units, the left-hand page explains the words and expressions to be studied in that unit. Where appropriate, it gives information about the meanings of words as well as how to use them. The right-hand page checks that you have understood the information on the left-hand page by giving you a series of exercises practising what you have just learnt. There is a key at the back of the book. It will help you learn more about expression studied in their unit. Some questions have only one correct answer. Other questions have more than one answer. You will find comments on the answers giving reasons why one answer may be more appropriate than another....